2019
DOI: 10.32615/ps.2019.086
|View full text |Cite
|
Sign up to set email alerts
|

Long-term high light stress induces leaf senescence in wheat (Triticum aestivum L.)

Abstract: In order to explore the association of long-term high light (HL) with leaf senescence in wheat, two wheat genotypes Xiaoyan 54 (HL-tolerant) and Jing 411 (HL-sensitive) grown in low light were subjected to HL for 2-8 d. The results showed that 6-8 d of HL led to dramatic decline of chlorophyll content, photochemical efficiency, and activity of Rubisco and antioxidant enzymes. Meanwhile, the content of malondialdehyde (MDA), soluble proteins, soluble sugars, superoxide anion, and ascorbic acid increased markedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…The results in Fig. 2 showed that LI, LT, and LL stresses caused the decrease in PN of strawberry leaves, while the Ci increased, indicating that under the above three adverse stresses, the decline of photosynthesis was not caused by a decrease in the supply of CO2 due to reduced gs, but was caused by nonstomatal limitations (such as the loss of Rubisco and photochemical activity) that hindered the utilization of CO2, resulting in the accumulation of intercellular CO2 (Allen and Ort 2001, Gerganova et al 2016, Liu et al 2019. Besides, the contents of total Chl also decreased by LI, LT, and LL stresses, and after recovery for 15 d, the total Chl content under LI and LT stresses returned to the control level, while this did not happen under LL stress ( Table 1).…”
Section: Discussionmentioning
confidence: 98%
“…The results in Fig. 2 showed that LI, LT, and LL stresses caused the decrease in PN of strawberry leaves, while the Ci increased, indicating that under the above three adverse stresses, the decline of photosynthesis was not caused by a decrease in the supply of CO2 due to reduced gs, but was caused by nonstomatal limitations (such as the loss of Rubisco and photochemical activity) that hindered the utilization of CO2, resulting in the accumulation of intercellular CO2 (Allen and Ort 2001, Gerganova et al 2016, Liu et al 2019. Besides, the contents of total Chl also decreased by LI, LT, and LL stresses, and after recovery for 15 d, the total Chl content under LI and LT stresses returned to the control level, while this did not happen under LL stress ( Table 1).…”
Section: Discussionmentioning
confidence: 98%
“…The OJIP curve contains mass information about the functional integrity of the photosynthetic electron transport chain (PETC), the primary site of ROS production in leaves under light (Brestic, Zivcak, Kalaji, Carpentier, & Allakhverdiev, 2012;Dou, Xv, Meng, Li, & Yang, 2015;Liu et al, 2019). The shape of the OJIP curve changed obviously in leaves of both ZD958 and XY335 after HT treatment (Figure 6a-d).…”
Section: Ht Treatment Restrained Photosynthetic Electron Transfer Amentioning
confidence: 99%
“…The antioxidant system maintains an optimal level of ROS [22] and protects cells and cell compartments against oxidative damage under various environmental stresses [41,42]. Besides the ascorbate-glutathione cycle, α-tocopherol, carotenoids, flavonoids, thioredoxins (TRXs), accumulation and stress symptoms in Arabidopsis [54] and pea [55] leaves, while prolonged HL stress had a similar effect in wheat (Figure 1b) [56]. The changes in ROS levels occur immediately after the exposure to HL and provide a signalling function in order to initiate various adaptive mechanisms, as demonstrated in Arabidopsis [57].…”
Section: Introductionmentioning
confidence: 97%